2006
DOI: 10.1073/pnas.0604078103
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic effects of membrane protein overexpression in Saccharomyces cerevisiae

Abstract: Large-scale protein overexpression phenotype screens provide an important complement to the more common gene knockout screens. Here, we have targeted the so far poorly understood Saccharomyces cerevisiae membrane proteome and report growth phenotypes for a strain collection overexpressing Ϸ600 C-terminally tagged integral membrane proteins grown both under normal and three different stress conditions. Although overexpression of most membrane proteins reduce the growth rate in synthetic defined medium, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
2
27
2
Order By: Relevance
“…We observed that most yeast membrane protein-GFP fusions expressed to higher levels under the GAL1 promoter than under the TEF promoter. Because the majority of membrane proteins when constitutively expressed retard cell growth (15), an inducible promoter such as GAL1 may be a better choice for overproduction in yeast. Moreover, most membrane protein-GFP fusions expressed better in the pep4 deletion strain FGY217, suggesting that some overexpressed proteins may be susceptible to vacuolar proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that most yeast membrane protein-GFP fusions expressed to higher levels under the GAL1 promoter than under the TEF promoter. Because the majority of membrane proteins when constitutively expressed retard cell growth (15), an inducible promoter such as GAL1 may be a better choice for overproduction in yeast. Moreover, most membrane protein-GFP fusions expressed better in the pep4 deletion strain FGY217, suggesting that some overexpressed proteins may be susceptible to vacuolar proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we estimated overexpression levels for 553 cloned S. cerevisiae polytopic membrane proteins by whole-cell Western blot analysis (15). From this collection, 20 proteins with expression levels ranging from 77 to 500 arbitrary units (the maximal expression recorded in the collection was 1,000 arbitrary units) were selected for the current study, the majority being transporters of various kinds [supporting information (SI) Table 1, top half].…”
Section: Selection Of Target Proteins and Strainsmentioning
confidence: 99%
“…Preparation of whole-cell lysates was done as described in ref. 28. Whole-cell lysates were subjected to SDS/PAGE and Western blotting with an HA antiserum.…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…We have earlier introduced a phenotyping approach for the quantitative extraction of these three physiological parameters from Saccharomyces cerevisiae deletion strains in environmental microculture arrays . The precision of the method allows not only the resolution of phenotypes into effects of different aspects of cellular physiology but also the quantification of marginal phenotypes not detectable by standard, more qualitative approaches Osterberg et al 2006).…”
Section: Introductionmentioning
confidence: 99%